Effect of shape and size of nickel‐coated particles fillers on conductivity of silicone rubber‐based composites. Issue 8 (19th April 2014) - Zhou, H.; Xia, Z.D.; Wang, X.Y.; Li, Z.; Li, T.T.; Guo, F.
<x xml:space="preserve">Abstract</x> Electrically conductive polymer composites have been widely used in recent years. The resistivity of the composites is influenced by several factors. The conductive silicone rubbers (CSRs) were prepared by adding the nickel‐coated graphite (Ni‐G) and/or nickel‐coated carbon fiber (Ni‐CF) into liquid silicon rubbers which were then subjected to the vulcanization. The effect of particle shape and size on the electrical conductivity of CSR was investigated; the results indicate that Ni‐CF filled CSR have lower percolation threshold than Ni‐G filled CSR. Compared to the filled particles with larger size, a higher amount of smaller particles are needed to form the same conductive pathway in CSR. Thus, there are more contact points in conductive pathway, which increase the total contact resistance. The volume resistivity of CSR can be significantly reduced by the doping of Ni‐CF particles, while the effect begins to wear off under high doping content. The fiber‐like Ni‐CF has a good "bridging" function for the formation of conductive pathway in CSR, which is greatly enhanced by increasing the length to diameter (l/d) ratio of Ni‐CF particles. Therefore, doping of the particles that have low percolation threshold can reduce the resistivity of the composites. POLYM. COMPOS., 36:1371–1377, 2015. © 2014 Society of Plastics Engineers